Lactoferrin concentration and expression in New Zealand cows milked once or twice a day. (15th January 2020) - Gedye, Kristene; Notcovich, Shirli; Correa‐Luna, Martin; Ariyarathne, Pavithra; Heiser, Axel; Lopez‐Lozano, Raquel; Lopez‐Villalobos, Nicolas
Abstract: This study evaluated the concentration and expression of lactoferrin (LF) in cows selected for once a day (OAD) milking compared to twice a day (TAD) milking. Milk samples were collected from the Massey University TAD and OAD herds. Milk traits and expression of LF and insulin‐like growth factor 1 (IGF‐1) were analyzed with a general linear model that included the fixed effects of milking frequency, lactation number, interaction between milking frequency and lactation number, and as covariates proportion of F, heterosis F × J and deviation from the herd median calving date. Cows milked OAD produced milk with higher ( p  < .01) concentrations of protein and lactose than TAD milked cows. Compared to TAD cows, cows milked OAD had higher expression of the LF gene (1.40 vs. 1.29 folds, p  = .03) and the IGF‐1 gene (1.69 vs. 1.48 folds, p  = .007). The correlation between the expression of LF gene and the concentration of LF in milk was strong ( r  = .66 p  < .001), but the correlation between the expression of the IGF‐1 gene and LF concentration was stronger ( r  = .94, p  < .001). These results suggest that milking frequency affects the milk composition and expression of milk composition genes at early lactation.